PENGARUH PENGEMBANGAN POTENSI DESA IHAMAHU DALAM UPAYA MENGATASI KEMISKINAN - Ludwina Pormes (P3M Politeknik Negeri Ambon, 2025)
This study was conducted with the aim of determining the extent of the influence of strengthening local potential in the village of Ihamahu through the development of local potential to help the people of Ihamahu village escape the cycle of poverty. It also aims to identify which variables have an impact on the poverty level.In this study, the independent variable used is the strengthening of local potential, while the dependent variable is the poverty level. Based on the calculation of simple linear regression analysis, the following can be observed:To determine the individual (partial) influence of the independent variable (strengthening of local potential) on the poverty level, a t-test was conducted. The result of the simple linear regression analysis showed a t-statistic value for the poverty level variable of -0.171. Meanwhile, the t-table at a significance level of 0.05 shows a value of 3.182.This indicates that the independent variable has a partially significant effect on the poverty level, meaning that strengthening local potential can significantly increase the poverty level. Based on the beta coefficient value and the calculated t-value, it is found that the variable influencing the poverty level is the strengthening of local potential, as it has a high t-value and beta coefficient. Keywords: Village Potential, Poverty